Object-oriented literary studies and Melville's cosmos: writing as dissemination in Moby-Dick. Issue 1 (2nd January 2022) - Lovasz, Adam
ABSTRACT: In a 2012 article, Graham Harman argues for an 'object-oriented' literary criticism. According to Harman's view, mainstream literary theory, exemplified in his account by New Criticism, New Historicism and Deconstructionism, tends to either place undue emphasis on the works themselves or, at the opposite extreme, to reduce works to being mere products of social conditions. Through an object-oriented, albeit non-realist reading of Herman Melville's renowned novel, Moby-Dick, or The Whale, I seek to bring Harman's object-oriented approach into a constructive debate with Jacques Derrida's deconstructionism. In particular, my goal is to show how examples of dissemination culled from Moby-Dick may be interpreted in an object-oriented manner. Derrida's theory of dissemination may be read in a fundamentally object-oriented, albeit non-realist way. Dissemination/s in the plural are productive moments that confront us with the emptiness of being and the pervasiveness of the vortex that sucks in all signifiers. Building on Michael Jonik's new materialist reading of Moby-Dick, I argue that a key theme of the novel is the empty, self-consuming aspect of reality. Real objects are unreal, and matter is hauntingly immaterial. Mutual interpenetration and cannibalistic intimacy without limit are just as real as the mutual separation affirmed by Harman.